Inspection and Numerical Analysis of an Ottoman Railway Bridge in Jordan - Amin H. Almasri; Qusai Fandi Al-Waked (Advances in Materials Science and Engineering)
The construction of bridges represents a big challenge, since they require enormous economic effort and specialized technical skills. Bridges were historically important as they help connecting people and thus diffusing cultures, sharing ideas, and providing the backbone of transportation networks. This study focuses on the inspection and structural analysis of a 20th-century Ottoman railway stone arched bridge located on the Hejaz railway network in Jordan. The bridge has a very important cultural heritage value which stems from its history. The bridge stone material was cut and tested to determine its strength, in order to be used in the analysis. The structural analysis was carried out to assess the structural condition of the bridge and its suitability for reuse. The study includes static analysis under gravity loads and seismic analysis under earthquake loads. Despite the existence of deterioration in the bridge body construction materials due to a combination of human and natural factors, the analysis results proved enough structural capability to sustain the imposed gravity loads, but not a strong earthquake.